BORDER POLICY IN PREVENTING HUMAN TRAFFICKING IN ACEH PROVINCE, INDONESIA - M. Gaussyah; M. Iqbal (Kanun Jurnal Ilmu Hukum, 2023)
This article examines how Aceh’s government border policy prevents human trafficking and its challenges. Act Number 43, 2008 on State’s Territory regulates the territorial borders of the state guaranteeing sovereignty and law-abiding in the territory, sovereignty, rights enforcement, and rules of managing state territory and its borders, including monitoring of borders. A Governor in every region bordering others must manage the region of borders and protect the territory, based on PERKA of the BNPP Number 4, 2019 on the Delegation of State’s Border Governance in the ambit of the Indonesia National Body for Governing Border (BNPP). This paper utilizes normative-emperical research methods, in order to analyses the issue in the law and its challenges in its application. Aceh provinces including some regional, including North Aceh, East Aceh, and Sabang borders is included in a bordering region with other states, which prone to human trafficking. The Aceh Government and Regionals/Municipals Governments has not issued the policy on governing the borders’ areas, so it is remain challenges in future. Additionally, a better coordination among the law enforcement agencies and establishing the territory and border offices at the provincial and district levels can help  to prevent human trafficking in Aceh Province.